Nerve Suture Combined With ADSCs Injection Under Real-Time and Dynamic NIR-II Fluorescence Imaging in Peripheral Nerve Regeneration in vivo - Dong, Shixian; Feng, Sijia; Chen, Yuzhou; Chen, Mo; Yang, Yimeng; Zhang, Jian; Li, Huizhu; Li, Xiaotong; Ji, Liang; Yang, Xing; Hao, Yuefeng; Chen, Jun; et al. (Frontiers in Chemistry, 2021)
Peripheral nerve injury gives rise to devastating conditions including neural dysfunction, unbearable pain and even paralysis. The therapeutic effect of current treatment for peripheral nerve injury is unsatisfactory, resulting in slow nerve regeneration and incomplete recovery of neural function. In this study, nerve suture combined with ADSCs injection was adopted in rat model of sciatic nerve injury. Under real-time visualization of the injected cells with the guidance of NIR-II fluorescence imaging in vivo, a spatio-temporal map displaying cell migration from the proximal injection site (0 day post-injection) of the nerve to the sutured site (7 days post-injection), and then to the distal section (14 days post-injection) was demonstrated. Furthermore, the results of electromyography and mechanical pain threshold indicated nerve regeneration and functional recovery after the combined therapy. Therefore, in the current study, the observed ADSCs migration in vivo, electrophysiological examination results and pathological changes all provided robust evidence for the efficacy of the applied treatment. Our approach of nerve suture combined with ADSCs injection in treating peripheral nerve injury under real-time NIR-II imaging monitoring in vivo added novel insights into the treatment for peripheral nerve injury, thus further enhancing in-depth understanding of peripheral nerve regeneration and the mechanism behind.